2018
DOI: 10.1002/gsj.1208
|View full text |Cite
|
Sign up to set email alerts
|

The boundaries of the firm in global strategy

Abstract: Research summary We briefly review the evolution in the analysis of the boundaries of the firm in global strategy. We explain how initial studies that argued that firm boundaries were driven by the minimization of transaction costs were later complemented by analyses that proposed that firm boundaries were driven by the development and use of resources to maximize value creation and capture. Studies of global strategy combine these two approaches and introduce the influence of location—both the home and host c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…It drives global digital technology emergence and markets. Our study supports the importance of knowledge in global linkages (Awate & Mudambi, 2018; Cuervo‐Cazurra, Mudambi, & Pedersen, 2018; Lorenzen & Mudambi, 2013; Mudambi, 2008; Turkina, Van Assche, & Kali, 2016). In finding “rich” international knowledge exchanges, we challenge the understanding that codified knowledge exchange is the focus of global ties argued on the basis of international differences and distance (Parkhe, 1991, 1998; Tallman & Phene, 2007).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…It drives global digital technology emergence and markets. Our study supports the importance of knowledge in global linkages (Awate & Mudambi, 2018; Cuervo‐Cazurra, Mudambi, & Pedersen, 2018; Lorenzen & Mudambi, 2013; Mudambi, 2008; Turkina, Van Assche, & Kali, 2016). In finding “rich” international knowledge exchanges, we challenge the understanding that codified knowledge exchange is the focus of global ties argued on the basis of international differences and distance (Parkhe, 1991, 1998; Tallman & Phene, 2007).…”
Section: Introductionsupporting
confidence: 84%
“…Knowledge exchanges and boundary spanning is important to global business (Awate & Mudambi, 2018; Cuervo‐Cazurra et al, 2018; Lorenzen & Mudambi, 2013; Mudambi, 2008; Pesch & Bouncken, 2017; Turkina et al, 2016). Global business can take advantage of the digital ties that face no spatial limits and allow network‐economies (Chu & Manchanda, 2016; Gawer & Phillips, 2013; Sawhney & Zabin, 2002).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the international business literature has revealed that firms' are increasingly making decisions to sell their products in many countries and meet multiple market demands or move, partially or entirely, production abroad (Grant 2016). Correspondingly, scholars have attempted to disentangle the antecedents (with a special focus on transactions, resources, locations, and institutions; Cuervo-Cazurra et al 2018, 2019Matysiak and Bausch 2012) and consequences (Kirca et al 2012) of this internationalization.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic supplementary material The online version of this article (https://doi.org/10.1057/s41267-019-00282-0) contains supplementary material, which is available to authorized users. 2016), the drivers influencing the decision of where to locate value activities and how to govern them (Bunyaratavej, Hahn, & Doh, 2007, 2008Cuervo-Cazurra, Mudambi, & Pedersen, 2018;Doh, Bunyaratavej, & Hahn, 2009;Giroud & Mirza, 2015), the effects of such ''fine-slicing'' on innovation processes (Andersson, Dasi, Mudambi, & Pedersen, 2016;Mudambi, 2008), as well as on factor prices and wages in host economies (Grossman & Rossi-Hansberg, 2008;Hummels, Jørgensen, Munch, & Xiang, 2014). 1 Thus far, researchers have assessed GVCs and its implications mainly relying on enterprise surveys, international trade statistics, and input-output (IO) models.…”
Section: Introductionmentioning
confidence: 99%